Penerapan Problem Based Learning Pada Pembelajaran Pendidikan Agama Islam Dan Budi Pekerti Kelas XII SMK Muhammadiyah Parung: Penerapan Problem Based Learning Pada Pembelajaran Pendidikan Agama Islam Dan Budi Pekerti Kelas XII SMK Muhammadiyah Parung - Giri Slamet Santoso Giri; Abdul Ghofur; Irfan Rizka Akbar (Journal of Research and Publication Innovation, 2023)
Problem Based Learning (PBM) or Problem Based Learning (PBL) is a learning model based on the principle of using problems as a starting point for the acquisition and integration of new knowledge. PBL is one of the student-centered learning models by confronting these learners with various problems faced in their lives. With this model of learning, students from the beginning have been faced with various life problems that they may encounter later when they graduate from school. PBL is one of the methods in the contextual learning model (Contextual Teaching and Learning) which is based on the theory of constructivism learning. The results showed that there are ten steps in implementing PBL. In addition, PBL can make it easier for students to better understand and master the learning materials for Islamic Religious Education and Ethics at SMK Muhammadiyah Parung because PBL can relate the knowledge that students get through learning at school to the problems of daily life. In addition, the results of this research also provide solutions that are expected to help educators to apply Problem Based Learning generally for all subjects and especially in the subjects of Islamic Religious Education and Ethics.